AN APPROACH TO MANAGEMENT EDUCATION: INTERDISCIPLINARY MODEL - Ahrens, Andreas; Zaščerinska, Jeļena; Melnikova, Julija; Andreeva, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
In business practice the paradigm has changed from global business to hybrid business. This shift requires a new quality of management education in order to bring out next-generation managers and leaders. The aim of the research is to shape an approach to management education through interdisciplinary research underpinning elaboration of a hypothesis on an innovative approach to preparing next-generation managers and leaders within management education. The meaning of the key concepts of “approach” and “principles” is studied. Moreover, the study demonstrates how the key concepts are related to the idea of “management education”. The study shows how the steps of the process are related following a logical chain: analysis of the terms “approach”, “principles” and “conditions” → approach to management education → conclusions. The novel contribution of this paper is the hypothesis on an innovative approach to preparing next-generation managers and leaders within management education.